Imidazole octasubstituted novel mono and double-decker phthalocyanines: Synthesis, characterization, electrical and gas sensing properties - DUMLUDAĞ, FATİH (PERGAMON-ELSEVIER SCIENCE LTD, 2018)
Imidazole disubstituted phthalonitrile (1) was prepared by the reaction of 4,5-dichlorophthalonitrile with 4,5-diphenyl-1H-imidazolethiole. Imidazole octasubstituted metal free (2), zinc(II) (3), cobalt(II) (4) monophthalocyanines and lutetium(III) (5) and europium(III) (6) double-decker phthalocyanines were prepared by cyclotetramerization of compound 1. The new compounds were characterized by H-1 NMR, C-13 NMR, UV-vis, IR, MALDI-TOF mass, ESR spectra and elemental analysis. Dc and ac conductivity and gas sensing properties (at room temperature) of the compounds of 2-6 were studied between the temperatures of 295-523 K. Ac conductivity values of the films were measured in the frequency region of 40 Hz-100 kHz. The films were tested for the vapors of toluene, ethanol, THF, n-hexane, chloroform and xylene. DC conductivity results revealed that the compounds 2-6 show a semiconductor behavior. Results of ac measurements show dominant conduction mechanism can be modeled depending on temperature and frequency. The best sensitivity values were obtained for the xylene vapors. The sensor 3 showed best sensitivity among the other sensors for xylene vapor. Response times of the sensors were also determined. (C) 2018 Elsevier Ltd. All rights reserved.
Keywords: Octasubstituted phthalocyanines; Imidazole; Gas sensor; Conductivity; VOC; LANGMUIR-BLODGETT-FILMS; SUBSTITUTED PHTHALOCYANINES; ELECTROCHEMICAL PROPERTIES; METAL-FREE; ZINC(II) PHTHALOCYANINES; TETRA-BENZIMIDAZOLE; ROOM-TEMPERATURE; THIN-FILMS; BALL; PORPHYRIN